Uji Aktivitas Antibakteri Krim Ekstrak Etanol Daun Kitolod (Isotoma longiflora)(L).C.Presl Terhadap Staphylococcus epidermidis dan Pseudomonas aeruginosa - Simanjuntak, Helen Anjelina; Nahampun, Laura Yunita; Purba, Hermawan; Simanjuntak, Herlina; Sinaga, Suharni Pintamas; Sembiring, Mahral Effendi; Rahmiati, Rahmiati; Situmorang, Toberni S (Herbal Medicine Journal, 2025)
Kitolod plants are used to treat various types of diseases, such as eye pain, wound healing, asthma, bronchitis, rheumatism and others. This study aims to determine the antibacterial activity test of kitolod leaf ethanol extract cream (Isotoma longiflora) (L).C.Presl against Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria. This research stage includes determination, preparation of simplicia, extraction, phytochemical screening, cream formulation F0 (0%), F1 (4%), F2 (6%) F3 (8%), and antibacterial test. The results of the phytochemical screening showed that alkaloids, flavonoids, tannins, saponins and steroids were obtained. The results of the antibacterial activity test of the formula against Staphylococcus epidermidis in sequence F0 (0%), F1 (4%), F2 (6%) and F3 (8%) were 11.315 mm; 15.205 mm; 18.843 mm; 23.698 mm. Meanwhile, against Pseudomonas aeruginosa bacteria, the measurements were 6.04 mm, 8.19 mm, 12.46 mm, and 17.24 mm, respectively. In conclusion, all variations of the cream formula showed antibacterial activity in inhibiting the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria. The cream formulation was more sensitive to Staphylococcus epidermidis bacteria than Pseudomonas aeruginosa bacteria.